Synthesis of molecular imprinting polymer (mip) heparin - Tharrishini A/P Athmanathan (School of Materials Engineering, University Malaysia Perlis, 2016)
This project is about the synthesis of molecular imprinted polymer (MIP) Heparin. From the previous studies, it has been discover that the heparin produced is not user-friendly and do not leads to green environment. So in order to overcome the current issue, this synthesis of MIP Heparin is being carried out. There are few factors will be discussed in the project and find out the best solution for MIP Heparin and make sure it is green environment based. The molecular imprinting of heparin is the new approach that is being studied. The non-covalent approach was used in preparation of MIP by sol gel method using two different size of silica gel. The micro-particles is characterized using Fourier Transform Infrared Spectroscopy (FTIR). The morphology of samples is determined by Scanning Electron Microscopy (SEM). A batch binding analysis is carried out to analyze the effect of size of silica gel on the binding performances of molecular imprinted polymer (MIP) and non-imprinted polymer (NIP). The MIP with 40-um silica gel have highest binding capacity and at the same time it showed the high imprinting factor. This is condition occurred due to high resemblance and more particular interconnection of template absorption.